THE DEVELOPMENT OF MATHEMATICS MODULE IN LINEAR EQUATION SYSTEM TWO VARIABLES MATERIAL WITH CONTEXTUAL APPROACH FOR GRADE VIII STUDENTS SMP / MTs - Queen Veronica Frieda Laurencia; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Limited learning resources is a problem that affects the achievement of learning goals. The school does not have a mathematics learning module with a contextual approach. This research aims to create modules as mathematics teaching materials and know the quality of the module in terms of the feasibility of content, presentation, and conformity with the contextual approach's characteristics and principles and know the students' responses to the mathematics module. The type of research is development research. This research model used is research and development that developed, including identifying potential and problem, collecting the information, designing a product, design validation, design revision, experiment, product revision, and product test. This research's subjects are teachers of mathematics, ICT teachers, and students. The object is The Development of Mathematics Module in Linear Equation System Two Variables Material with Contextual Approach for Grade VIII Students SMP/ MTs. The type of data used is qualitative data, which is then converted into quantitative data. The data collecting technique used is the form of interviews and questionnaires. The instrument tests are performed by material experts, media experts, and students. The data analysis used is descriptive analysis, and questionnaire analysis. Based on the research results obtained from material experts' assessment, an average score is 129.33 included in the very good category, the assessment of media experts an average score is 136.33 included in the very good category. Student responses to the module indicate that an average score is 133.86 included in the very good category. Based on the assessment of research from material experts, media experts, and students' responses to the development of mathematics modules in line are equation system two variables material with a contextual approach for grade VIII students, SMP/MTs is feasible the learning process.